DisDiscrete Controlled Bi Frequency Boost Convertercrete Controlled Bi Frequency Boost Converter - Vijayalakshmi, S; Marimuthu, M; Srimathi, A; Gomathi, M; Banu, A P Ayisha (International Journal of Psychosocial Rehabilitation, 2020)
A digital PID controller has been modeled for a Double frequency boost converter. The proposed converter is composed of two cells. One cell operates under high frequency and another cell operates under low frequency. Without the accumulation of extra control circuits, the converter can work at a very high switching frequency. The static and transient response of the proposed converter is enhanced and the switching loss of the converter is small. A discrete compensator incorporated with PID control algorithm enhances the dynamic response of the closed loop system. Double frequency boost converter with closed loop controller is simulated using MATLAB / Simulink and switching loss across the switches are found using pSpice software.